The effect of COVID-19 on local government policy implementation: Declines in police reports of domestic violence during lockdowns - Jeremy A. Cook; Timothy W. Taylor (Journal of Government and Economics, 2023)
We document a reduction in police reporting of domestic violence during shelter-in-place (SIP) orders issued by city governments in March and April of 2020. Using data from 18 large U.S. city police departments, we exploit the unique timing of city-specific SIP orders to identify a decrease as high as 11 percent in police reports of domestic violence. Lockdowns, explicitly designed to reduce contact among civilian populations, may also lead to reduced contact between emergency responders and civilians. Our findings suggest police change their own behaviors in response to government-issued SIP orders leading to a decrease in agency reports of domestic violence. While previous scholarship on domestic violence has found an increase in emergency calls for service from households during SIP, we consistently find a decrease in police reporting of domestic violence. By centering our analysis on the responses of law enforcement agencies, we highlight the divergence in the consequences of SIP orders on household behaviors versus institutional behaviors. We present robust findings using event studies in addition to both staggered treatment and conventional difference-in-differences estimators. The implications of our study extend to city officials who are tasked with assessing the unique repercussions of SIP orders on both households and the responsiveness of local government agencies. This research underscores the multifaceted nature of the effects induced by external shocks such as COVID-19, shedding light on the intricate interplay between societal dynamics and institutional responses.